KEPUASAN MAHASISWA KPI IAIN SURAKARTA DALAM PEMILIHAN KONSENTRASI PROGRAM STUDI - Eny Susilowati; Rhesa Zuhriya Briyan Pratiwi (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2018)
This research aims to measure the satisfaction of KPI’ students of IAIN Surakarta in selecting Department concentration through the influence of motives and satisfaction in selecting Department concentration. Using quantitative descriptive method, subjects of this research were 2014 KPI’ students. Data collection were taken by observation, questionnaire, and documentation. For variables, it leads to independent variable about the motive of the 2014 KPI’ students in choosing concentration, and dependent variable related to the level of student satisfaction. Based on result of analysis, cognitive needs are aspects of the needs variable affect the level of student satisfaction in choosing KPI’s Department concentration. Related to this, cognitive aspects are basic needs in the process of student’s knowledge and experience that affect the satisfaction level of selecting concentration, because it deals with efforts to understand the academic and potential factors of students in developing interests and talents in the field of communication.